EXPERIMENTAL STUDY OF FE-MG DISTRIBUTION BETWEEN BIOTITE AND ORTHOPYROXENE AT P=490 MPA - Fonarev V.I.; Konilov A.N. (My University, 1986)
Partitioning of Mg and Fe between coexisting biotite and orthopyroxene has been experimentally determined at temperatures 700, 750 and 800° C and 490 MPa total pressure in the system KAlO2-MgO-FeO-SiO2-H2O. Oxygen fugacity was controlled by the QFM buffer. Starting materials were synthetic minerals of differing Fe/(Fe+Mg) values. Run products were analyzed for partitioning of components by a microprobe. Orthopyroxene was established to be notably inhomogeneous, whereas biotite was essentially homogeneous. To establish equilibrium relations, statistical treatment of the results of each experiment in addition to the whole complex of experimental data was applied. The regression equations for isotherms of the Fe-Mg partitioning between the minerals studied have been obtained. As a result, the equation for a two-dimensional regression may be written as: Y=(A+A1t+A2t2)(X−X4)+(B+B1t+B1t2)(X2−X4)+(C+C1t+C1t2)(X3−X4)+X4 where Y=XFeOpx; X=XFeBi;t=1000/T,K,A= 4.59398,B=−11.13731,A= 8.25072,A1=− 8.29838,B1= 28.19304,C1=−20.80485,A2= 4.97316,B2=−20.98240,C2= 15.35967 σ=0.0143 . This equation enables extrapolation of partitioning isotherms over a wide range of temperatures.